IMPLIKATUR DALAM NOVEL DEAR NATHAN KARYA ERISCA FEBRIANI (KAJIAN PRAGMATIK) - Ranti Minhaqillah; Eli Syarifah Aeni; Agus Priyanto (IKIP Siliwangi, 2022)
The utterances that occur in every dialogue in the novel often have various purposes or intentions that are certainly not the same as the real one. Likewise, conversations in novels cannot be separated from the power of imagination built by the author which makes the reader have to analyze the hidden meanings in each story. Thus, it can be said that the speech in every dialogue of the novel has an implied purpose. This research is an implicature study through the use of pragmatic studies which aims to describe the types of implicatures in the novel